CD73: agent development potential and its application in diabetes and atherosclerosis - Liu, Dan; Zhao, Jingjing; Li, Ling; Wang, Jie; Wang, Chao; Wu, Yudong; Huang, Yucun; Xing, Dongming; Chen, Wujun (Frontiers in Immunology, 2024)
CD73, an important metabolic and immune escape-promoting gene, catalyzes the hydrolysis of adenosine monophosphate (AMP) to adenosine (ADO). AMP has anti-inflammatory and vascular relaxant properties, while ADO has a strong immunosuppressive effect, suggesting that CD73 has pro-inflammatory and immune escape effects. However, CD73 also decreased proinflammatory reaction, suggesting that CD73 has a positive side to the body. Indeed, CD73 plays a protective role in diabetes, while with age, CD73 changes from anti-atherosclerosis to pro-atherosclerosis. The upregulation of CD73 with agents, including AGT-5, Aire-overexpressing DCs, Aspirin, BAFFR-Fc, CD4+ peptide, ICAs, IL-2 therapies, SAgAs, sCD73, stem cells, RAD51 inhibitor, TLR9 inhibitor, and VD, decreased diabetes and atherosclerosis development. However, the downregulation of CD73 with agents, including benzothiadiazine derivatives and CD73 siRNA, reduced atherosclerosis. Notably, many CD73 agents were investigated in clinical trials. However, no agents were used to treat diabetes and atherosclerosis. Most agents were CD73 inhibitors. Only FP-1201, a CD73 agonist, was investigated in clinical trials but its further development was discontinued. In addition, many lncRNAs, circRNAs, and genes are located at the same chromosomal location as CD73. In particular, circNT5E promoted CD73 expression. circNT5E may be a promising target for agent development. This mini-review focuses on the current state of knowledge of CD73 in diabetes, atherosclerosis, and its potential role in agent development.